2016
DOI: 10.1007/s13361-016-1472-3
|View full text |Cite
|
Sign up to set email alerts
|

HAMS: High-Affinity Mass Spectrometry Screening. A High-Throughput Screening Method for Identifying the Tightest-Binding Lead Compounds for Target Proteins with No False Positive Identifications

Abstract: A major challenge in drug discovery is the identification of high affinity lead compounds that bind a particular target protein; these leads are typically identified by high throughput screens. Mass spectrometry has become a detection method of choice in drug screening assays because the target and the ligand need not be modified. Label free assays are advantageous because they can be developed more rapidly than assays requiring labels, and they eliminate the risk of the label interfering with the binding even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…While the data in Fig. 5 do not say which compound in Library B was the strong binder, we have previously demonstrated that this inhibitor (ethoxzolamide) can easily be identified as the strong binder in a batch of ~400 compounds, using the recently published HAMS screening method, where the highest-affinity ligand (of the 400 in the well) is identified in a complementary screen 26 .
Figure 5 Screening assay for CA binders with methoxzolamide as the reporter molecule.
…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…While the data in Fig. 5 do not say which compound in Library B was the strong binder, we have previously demonstrated that this inhibitor (ethoxzolamide) can easily be identified as the strong binder in a batch of ~400 compounds, using the recently published HAMS screening method, where the highest-affinity ligand (of the 400 in the well) is identified in a complementary screen 26 .
Figure 5 Screening assay for CA binders with methoxzolamide as the reporter molecule.
…”
Section: Resultsmentioning
confidence: 93%
“…For many druggable targets, binding compounds are known, and we provide three relevant examples herein. For a protein with no known binding compounds, a complementary assay could be used to identify a weak-binding reporter molecule 26 .
Figure 1 Experimental workflow.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations